Pengaruh Kepemilikan Institusional, Media Exposure dan Gender Diversity terhadap Pengungkapan Corporate Social Responsibility - Ramadhani, Radhika; Taqwa, Salma (Jurnal Nuansa Karya Akuntansi, 2024)
The more a company develops, the more it has an impact on the social side of society and environmental damage, therefore the existence of Corporate Social Responsibility shows how companies pay attention to environmental and social issues. This is manifested in the company's practices and policies towards its social environment in the form of ethical behavior and transparency of activities and information related to Corporate Social Responsibility. This study was conducted to determine the effect of institutional ownership, media exposure, and gender diversity on corporate social responsibility disclosure in manufacturing companies listed on the Indonesia stock exchange in 2017-2021. With a population of 72 manufacturing companies listed on the Indonesia stock exchange in 2017-2021 which were selected using purposive sampling method, a sample of 360 was obtained. Multiple regression analysis was used as a data analysis technique until the results obtained that institutional ownership and gender diversity have no effect on corporate social responsibility disclosure but media exposure can affect corporate social responsibility disclosure.